Analysis of Coastal Tourism Development Strategy in Indonesia to Improve Community Economy - Yahya, Nurul Fajriah; Sahabuddin, Romansyah; Amin, Andi Nurzakiah; Sulolipu, Andi Annisa (PT. Maju Malaqbi Makkarana, 2024)
Coastal tourism plays a crucial role in Indonesia’s economic growth, particularly in enhancing local community welfare. This study aims to analyze effective strategies for developing coastal tourism to improve the community’s economy. Using a qualitative approach, data were collected through interviews, observations, and document analysis in selected coastal tourism areas. The findings reveal that sustainable tourism development, community empowerment, and digital marketing adoption significantly contribute to economic improvement. However, challenges such as inadequate infrastructure, environmental degradation, and policy inconsistencies hinder optimal development. The study suggests a collaborative approach involving government, local communities, and private sectors to establish sustainable and inclusive coastal tourism strategies. Strengthening infrastructure, promoting eco-tourism, and enhancing digital tourism platforms are recommended to maximize economic benefits. These findings provide insights for policymakers and stakeholders to formulate more effective coastal tourism policies in Indonesia.